Photosynthetic Conversion of CO2 Into Pinene Using Engineered Synechococcus sp. PCC 7002 - Yang, Ruigang; Zhu, Lingyun; Li, Tao; Zhu, Lv-yun; Ye, Zi; Zhang, Dongyi (Frontiers in Bioengineering and Biotechnology, 2021)
Metabolic engineering of cyanobacteria has received much attention as a sustainable strategy to convert CO2 to various longer carbon chain fuels. Pinene has become increasingly attractive since pinene dimers contain high volumetric energy and have been proposed to act as potential aircraft fuels. However, cyanobacteria cannot directly convert geranyl pyrophosphate into pinene due to the lack of endogenous pinene synthase. Herein, we integrated the gene encoding Abies grandis pinene synthase into the model cyanobacterium Synechococcus sp. PCC 7002 through homologous recombination. The genetically modified cyanobacteria achieved a pinene titer of 1.525 ± 0.l45 mg L−1 in the lab-scale tube photobioreactor with CO2 aeration. Specifically, the results showed a mixture of α- and β-pinene (∼33:67 ratio). The ratio of β-pinene in the product was significantly increased compared with that previously reported in the engineered Escherichia coli. Furthermore, we investigated the photoautotrophic growth performances of Synechococcus overlaid with different concentrations of dodecane. The work demonstrates that the engineered Synechococcus is a suitable potential platform for β-pinene production.